IMPLIKASI EKONOMI ULOS HOLONG BAGI PENGANTIN BATAK TOBA: PENDEKATAN UTILITAS DAN BIAYA OPORTUNIS - Purba, Elvis Fresly; Lastri (UNIKA Santo Thomas, 2022)
The aim of this study is to describe the tradition of ulos holong, that the offering of ulos for bride/groom in every Toba Batak wedding ceremony in Medan, creates an economic impact on the bridegroom. The research was carried out in three sub-districts in two stages of time, that is September 2019 – February 2020 (before the Covid-19 pandemic) and September 2020 to February 2021 (during the Covid-19 pandemic). The sampling method was carried out by accidental sampling by selecting 30 families at each stage of the study. The results showed that all respondents sold most of the received ulos because the utility or use value of the ulos for bride and grooms was very limited. This is a practical and rational choice because the proceeds from the sale (cash) are more useful than ulos, especially in the short term. Meanwhile, implementing ulos tinonun sadari can also be a more practical and economical option as a substitute for ulos holong. However, because ulos holong is still maintained, so that from opportunity cost approach, this tradition has still an economic impact on the bride and groom. The value is the difference between the value of the ulos tinonun sadari which should be received by the bride/grooms from the proceeds of the sale of ulos holong. So, by maintaining the ulos holong tradition, the bride and grooms “lose income” several million rupiah for each traditional wedding ceremony. The value is greater before the pandemic period than during the pandemic.